Skizo Studios Graphic Designing / Nur Aifaa Amir Murad - Nur Aifaa, Amir Murad (2020)
Skizo Studios is created because of my passion towards arts. To be specific, designing arts. I love to design. I have been designing things since my childhood. I decided to choose to be a designer because I live to solve problems, and a graphic designer even more because I love to solve visual ones. For some reason I felt very content when my customers are happy with my designing even if I need to stay up all night until dawn just to create the perfect logo, word mark, layout that when I present it, it was all worth it. Other than that, by becoming a designer I get the chance to express myself in the work I do. I believe one can do a good job on any position only if they love what they do and I love to do design various things, so my choice is obvious. Aside from my passion, this kind of business is not common and people often having a hard time finding a designing business here, around Sitiawan therefore I decided to start this business here. Skizo Studios describes the sketching and designing service which I offered to my customers. Its motto is “Brings creativity within you” which exactly describes my job as a designer when I assist my client to turn their idea into reality. My company vision is to be the number one designing studio which gathers the most talented designers around Malaysia and create the most successful designing company in the world. Our mission is to deliver the highest quality of various designing works filled with innovation, ingenuity and imagination. Skizo Studios prides itself on its high-quality designers who deliver only the best graphic design services. Whether you're looking for a spectacular new logo, some stunning flyers, new business cards or any kind of designing works, our talented global community of designers at Skizo Studios can make it happen. Skizo Studios customer segment is small business entrepreneur for business logo, card, brochure and website design. Other than that, normal customers that wanted a custom design for their clubs or any other things aside logos are welcomed. As for university, school students or any teenagers for jersey, t-shirt and resume template design. Lastly, with our affordable pricing we would be the first choice of the people